2001
DOI: 10.1108/13639510110382241
|View full text |Cite
|
Sign up to set email alerts
|

The influence of grip strength on handgun marksmanship in basic law enforcement training

Abstract: This study investigated the influence of grip strength on semi-automatic handguns in basic law enforcement training. The grip strength and marksmanship scores of police recruits were measured. All the recruits underwent the same basic firearms training and about half the recruits were given a Grip Master to exercise with in the hope of improving their grip strength. The grip strength improvement was similar for recruits with and without Grip Master. Both groups significantly improved their marksmanship by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 5 publications
4
41
0
1
Order By: Relevance
“…Hence, these results are in accordance with Mon-López, Tejero-González and Calero [3] who show that men obtain better results in the pistol event than women. Moreover, in other disciplines such as police shooting, men outperformed women [8] as well as with other calibres like 9mm pistol, where men performed better than women [9]. Contrary to these results, Vučković, Dopsaj, Radovanović and Jovanović [10] only found performance differences between genders at the beginning of a pistol training programme.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Hence, these results are in accordance with Mon-López, Tejero-González and Calero [3] who show that men obtain better results in the pistol event than women. Moreover, in other disciplines such as police shooting, men outperformed women [8] as well as with other calibres like 9mm pistol, where men performed better than women [9]. Contrary to these results, Vučković, Dopsaj, Radovanović and Jovanović [10] only found performance differences between genders at the beginning of a pistol training programme.…”
Section: Discussionmentioning
confidence: 91%
“…Contrary to these results, men performed better than women in other sports [6], and specifically in shooting, women fatigue more than men when firing with certain types of rifles [7]. Moreover, policemen performed better than policewomen with guns [8], and men performed better with 9mm pistols than women [9]. However, these results contrast with those of Vučković et al [10] who only found performance differences between genders at the beginning of a pistol training programme.…”
Section: Introductionmentioning
confidence: 77%
“…Grip strength for each hand was measured by a hand grip dynamometer (Takei Scientific Instruments, Japan) with procedures adapted from law enforcement research (6,12,18,28).…”
Section: Grip Strengthmentioning
confidence: 99%
“…Recruits kept their testing arm by their side throughout the assessment (6), and squeezed the handle as hard as possible for approximately 2 s (31). One attempt was completed for each hand (12), the left hand was tested first for all recruits, and the score was recorded to the nearest kilogram (kg).…”
Section: Grip Strengthmentioning
confidence: 99%
“…Recruits will therefore be able to clarify tasks, identify potential performance problems, choose effective tactics, improve gross motor skills to influence grip strength, learn stimuluscoordinated responses so as to learn to respond automatically to and survive deadly force encounters [12,26,37]. For better performance, the orientation of visual attention and the motor components of a task should be tightly coupled [8].…”
Section: Resultsand Discussionmentioning
confidence: 99%